Isolation, Molecular Characterization, and Antibiotic Resistance of Avian Pathogenic Escherichia coli in Eastern China - Dossêh Jean Apôtre Afayibo; Hong Zhu; Beibei Zhang; Lan Yao; Hosny Ahmed Abdelgawad; Mingxing Tian; Jingjing Qi; Yali Liu; Shaohui Wang (Veterinary Sciences, 2022)
Avian pathogenic Escherichia coli (APEC) causes colibacillosis in avians, resulting in considerable losses in the poultry industry. APEC showed zoonotic potential initially related to the fact that APEC serves as the reservoir of virulence genes and antibiotic resistance genes for other E. coli. Thus, we determine the serotypes, phylogenetic groups, virulence genes distribution, and antibiotic resistance profiles of APEC isolates in eastern China. A total of 230 APEC were isolated from diseased chicken and duck with typical colibacillosis symptoms. Serotyping identified that O78 (44.78%) was the predominant serotype. The majority of APEC isolates were classified into B2 (29.57%), A (26.96%), D (20.00%), and B1 (18.26%), respectively. Among the 15 virulence genes, a high prevalence of ibeB (99.57%), fimC (91.74%), mat (91.30%), ompA (83.04%), and iss (80.43%) genes was observed. Except for low resistance rates for imipenem (1.7%) and polymyxin B (0.4%), most of the APEC isolates were resistant to erythromycin (98.7%), enrofloxacin (96.1%), tetracycline (95.2%), doxycycline (93.9%), lincomycin (90.0%), and streptomycin (90.0%). Moreover, all APEC exhibit multi-drug resistance. This study indicated that APEC isolates harbor a variety of virulence genes and showed multi-antibiotic resistance profiles, providing proof for understanding the epidemiological background and zoonotic potential of APEC in poultry farms.